Earleria panicula - Gil, Marta; Ramil, Fran; Agís, José Ansín (Zenodo, 2020)
Earleria panicula (G.O. Sars, 1874) Campanulina panicula : Cornelius, 1995a: 190–192, fig. 43. Opercularella panicula : Christiansen, 1972: 291–292; Leloup, 1974: 4–6, fig. 3; Ramil & Iglesias, 1988: 79–81, figs. 1–2; Ramil & Vervoort, 1992: 25–27, fig. 3. Opercularella denticulata : Gili et al. 1989: 75–76, fig. 6A. Racemoramus panicula : Calder, 2012: 26, fig. 24. Earleria quadrata : Schuchert et al . 2017: 177, figs. 5–6. Material examined. MAURIT-0911, stn MUDR02, 16º08´50”N, 16º57´01”W, 462 m, 5-XII-2009: one colony, badly damaged, no gonothecae. MAURIT-0911, stn MUDR07, 18º35´40”N 16º43´12”W, 460 m, 12-XII-2009: one colony, without gonothecae. Biology. The species can colonize a great variety of substrata, such as hydroids, brachiopods, pennatulids, bivalves, dead corals, polychaete tubes and ascidians (Cornelius 1995a; Calder 2012). Fertile colonies have been found in April, June, August, November and December (Ramil & Vervoort 1992; Gili et al. 1989; Cornelius 1995a; Gil & Ramil 2017a). Gonothecae were not found in our material. Distribution. Earleria panicula , including its synonyms Campanulina denticulata Clarke, 1907 and Campanulina indivisa Fraser, 1948, was considered to be widely distributed in the Atlantic, Pacific and Indian Oceans at moderately deep to deep waters (Ramil & Vervoort 1992). Nevertheless, Calder (2012) considered the material from the Pacific and Indian Oceans to be a different species ( Racemoramus denticulata ), and, in consequence, the current distribution of E. panicula is restricted to the East Atlantic, from Trondheimfjord, Norway (Calder 2012) to at least Namibia [Gili et al. 1989, as Opercularella denticulata (Clarke, 1907)]. In West Africa, it was collected from Morocco [Ramil & Vervoort 1992, as Opercularella panicula (Sars, 1874)] and Mauritania (Gil & Ramil 2017a). The bathymetric distribution of the species ranges from 30 to 2100 m (Christiansen 1972; Ramil & Vervoort 1992). Our material was collected from depths of 460 to 462 m. Remarks. The material was composed of two colonies with monopodial growth and a cluster of monosiphonic, unsegmented and straight branches with badly damaged terminal hydranths. This morphology was consistent with the typical structure of E. panicula , a species previously recorded in Mauritanian soft bottoms (Gil & Ramil 2017a, as R. panicula ). Moreover, the Mauritanian material is identical to those reported by Ramil & Vervoort (1992) from the Alboran Sea and Ibero-Moroccan Gulf to off Casablanca. Recently, Schuchert et al. (2017) used DNA barcoding and found that Earleria quadrata (Hosia & Pagès, 2007) is the medusa of E. panicula . However, differences in the geographical distribution of the medusa, only known in deep waters of Korsfjord (Norway), and the polyp phase, which is widely distributed in the East Atlantic, led Schuchert et al. (2017) to consider the identity of E. panicula ambiguous, since it could represent a species complex. Nevertheless, samples of Racemoramus panicula from the Alboran Sea and Gulf of Cádiz showed 16S sequences almost identical to that of E. quadrata (Schuchert et al. 2017), which seems to supports its co-specificity in at least the Northeast Atlantic. Despite Schuchert et al. (2017) hesitate to synonymise both names, currently they are considered the same species (Schuchert 2018). : Published as part of Gil, Marta, Ramil, Fran & Agís, José Ansín, 2020, Hydroids (Cnidaria, Hydrozoa) from Mauritanian Coral Mounds, pp. 412-466 in Zootaxa 4878 (3) on page 422, DOI: 10.11646/zootaxa.4878.3.2, http://zenodo.org/record/4425132 : {"references": ["Sars, G. O. (1874) Bidrag til Kundskaben om Norges Hydroider. Forhandlinger i Videnskabs-Selskabet i Kristiana, 1873, 91 - 150.", "Cornelius, P. F. S. (1995 a) North-West European Thecate Hydroids and their Medusae. Part 1. Part 1. Introduction, Laodiceidae to Haleciidae. Synopses of the British Fauna, New Series, 50, 1 - 347.", "Christiansen, B. O. (1972). The hydroid fauna of the Oslo Fjord in Norway. Norwegian Journal of Zoology, 20, 279 - 310.", "Leloup, E. (1974) Hydropolypes calyptoblastiques du Chili. Report no. 48 of the Lund University Chile Expedition 1948 - 1949. Sarsia, 55, 1 - 62. https: // doi. org / 10.1080 / 00364827.1974.10411252", "Ramil, F. & Iglesias, A. (1988) Sobre la presencia de Opercularella panicula (Sars, 1873) (Cnidaria, Hydrozoa) en las costas de la Peninsula Iberica. Thalassas, 6, 79 - 82.", "Ramil, F. & Vervoort, W. (1992) Report on the Hydroida collected by the \" BALGIM \" expedition in and around the Strait of Gibraltar. Zoologische Verhandelingen, Leiden, 277, 1 - 262.", "Gili, J. M., Vervoort, W. & Pages, F. (1989) Hydroids from the West African coast: Guinea Bissau, Namibia and South Africa. Scientia Marina, 53 (1), 67 - 112.", "Calder, D. R. (2012) On a collection of hydroids (Cnidaria, Hydrozoa, Hydroidolina) from the west coast of Sweden, with a checklist of species from the region. Zootaxa, 3171 (1), 1 - 77. https: // doi. org / 10.11646 / zootaxa. 3171.1.1", "Schuchert, P., Hosia, A. & Leclere, L. (2017) Identification of the polyp stage of three leptomedusa species using DNA barcoding. Revue suisse de Zoologie, 124 (1), 167 - 182.", "Gil, M. & Ramil, F. (2017 a) Hydrozoans from Mauritanian Deep-Waters. In: Ramos, A., Ramil, F. & Sanz, J. L. (Eds.), Deep sea ecosystems off Mauritania: Researching marine biodiversity and habitats in West African Deep-waters. Springer, Dordrecht, pp. 419 - 444. https: // doi. org / 10.1007 / 978 - 94 - 024 - 1023 - 5 _ 11", "Schuchert, P. (2018) World Hydrozoa Database. Earleria panicula (G. O. Sars, 1874). Available from: http: // www. marinespecies. org / hydrozoa / aphia. php? p = taxdetails & id = 1255613 (accessed 3 September 2020)"]}